Roadmap for emerging cyberbullying mitigation: integrating AI-based solutions, ethics, and policy - Mahmood, Atif; Shabana Anjum, Shaik; Shah, Umm E Mariya; Cherukuru, Pavani; Iqbal, Javid; Bukhari, Sarah (2025)
Cyberbullying is one of these challenges that are most found among the younger users of social media which affects the mental health. Artificial Intelligence (AI) is rapidly developing and has enormous potential to mitigate cyberbullying. Therefore, this chapter will talk about the role AI has started playing in strengthening the efforts to combat cyberbullying. Cyberbullying includes all forms of deliberate aggressive behaviour that aims to inflict social, psychological or physical pain in a digital space and AI detection technologies have a lot of potential to detect, predict and prevent cyberbullying in real time. Other critical components of the chapter are how the advances in Natural Language Processing (NLP) technologies, machine learning, images and videos, behavioural analytics make AI an emerging innovation to prevent cyberbullying and provide better services in a timely manner. There are positive trends that make it clear how Safer AI can help in improving the safety of future digital environments. More advanced NLP models will be able to identify the nuances of cyberbullying involving indirect attacks and sarcasm. The chapter will also discuss the hazards associated with AI-based solutions, such as privacy, the zero-sum game of AI morality against AI effectiveness, and the importance of explaining and assigning responsibility for every AI decision. It shows how AI is changing our approach to online safety and helps us identify cyberbullying in a variety of media, including text, video and images. This article gives an overview of roadmap for cyberbullying mitigation with the assistance of AI and ethical practices.